YOUTUBE AS INSTRUCTIONAL MEDIA IN PROMOTING EFL INDONESIAN STUDENTS’ PRONUNCIATION - Suwastini, Ni Komang Arie; Rastari, Kadek Lelyana; Suarcaya, Putu (Polyglot, 2023)
AbstractPronunciation for Indonesian EFL students is tricky and challenging due to the different phonetic systems of the student's mother tongue and the target language. Integrating YouTube into English language learning could overcome these issues. The present study reviewed previous studies about the benefits of integrating YouTube as instructional media in promoting EFL students' pronunciation. This study was library research following George's (2008) model by selecting recent publications on the topic to summarize how YouTube videos affect students' English pronunciation and highlight a research gap that could be taken by future research. The review revealed that YouTube had benefitted students in aspects of pronunciation: stress, intonation, rhythm, voice quality, gestures, vowels, and consonants, although research on the application's use for improving students' rhythm is minimal despite the availability of relevant videos. This finding implies the need for more research on improving students' rhythm using YouTube video. Bahasa Indonesia AbstrakPengucapan bahasa Inggris sangat rumit untuk pebelajar Indonesia karena perbedaan dalam sistem fonetik bahasa ibu dan bahasa target siswa. Integrasi video YouTube ke dalam pembelajaran bahasa Inggris dapat mengatasi masalah ini. Kajian ini mencermati hasil penelitian terkini mengenai integrasi video YouTube sebagai media pembelajaran untuk meningkatkan pelafalan bahasa Inggris siswa. Penelitian ini merupakan kajian pustaka menggunakan model dari George (2008), dengan melibatkan peneitian terkait untuk menghasilkan gambaran umum mengenai pengaruh video Youtube terhadap pelafalan siswa untuk menyoroti kesenjangan penelitian yang masih ada sehingga menjadi masukan untuk penelitian selanjutnya. Ditemukan bahwa Youtube meningkatkan pelafalan siswa dari tekanan, intonasi, ritme, kualitas suara, gestur, pelafalan suara vokal dan konsonan. Namun, penelitian yang menyoroti pemanfaatan Youtube untuk meningkatkan ritme dalam pelafan siswa masih terbatas, walaupun Youtube menyediakan banyak video yang relevan. Temuan ini berimplikasi pada perlunya penelitian lebih lanjut mengenai pemanfaatan video YouTube untuk mengembangkan ritme pelafalan bahasa Inggris siswa.